Analisis Perbandingan Penyusutan Aktiva Tetap Berdasarkan Standar Akuntansi Keuangan Dan Perpajakan Serta Dampaknya Terhadap Laporan Keuangan Pada PT. Sumber Usaha Rizkila Medan - Yus Epi,S.E, M.Ak Epi,S.E, M.Ak (AGHNIYA : Jurnal Ekonomi Islam, 2019)
This final project aims to find out about the analysis of the comparison of depreciation offixed assets based on GAAP and taxation and the impact on financial statements at PT.Business Source Rizkila Medan. Find out and understand how the calculation of depreciationexpense based on SAK with tax calculation and how the impact of the calculation expense ondepreciation expense on the company's financial statements. And from the results of the studyshow that the calculation of depreciation expense according to SAK and taxation causeslosses in the company's income statement and on the balance sheet shows that the fixed assetsowned by the company are relatively large, while the capital change report shows that thecompany has large capital when starting its business .